Characterisation of cultivated breeding lines of eggplant (Solanum melongena L.) and related wild Solanum species from India. Issue 1 (2nd January 2016) - Premabati Devi, Chingakham; Munshi, Anilabha D.; Behera, Tusar Kanti; Choudhary, Harshwardhan; Saha, Partha
ABSTRACT: Immature fruit of cultivated species of eggplant ( Solanum melongena L.) are commonly used as a summer vegetable in India. Rich morphological variation exists among the cultivated species of eggplant in different growing regions of the country. We have characterised 24 breeding lines of Solanum spp., including 20 eggplant cultivars and four wild species of eggplant, based on 13 morphological characters using Mahalonabis D 2 statistics. All 24 breeding lines of Solanum spp., including the 20 eggplant cultivars and four wild species, were grouped into four clusters by agglomerative clustering. Cluster II and Cluster IV contained the most accessions (eight each), while Cluster I and Cluster III had four accessions each. The highest inter-cluster (D 2 ) distance (158.33) was observed between Cluster I and Cluster II, followed by Cluster I and Cluster III (108.48), and Cluster II and Cluster IV (102.96), which indicated that accessions in Cluster I and Cluster II were more divergent than those in the other clusters. The highest intra-cluster distance (5.80) was observed in Cluster IV, with eight genotypes, and the lowest intra-cluster distance (2.21) was observed in Cluster II, also with eight genotypes. The intra-cluster distances in all four clusters were lower than the inter-cluster distances, which indicated that genotypes within the same cluster were closely related. Genotypes in Cluster IV had the maximum number of flowers per cluster (3.63), the highest number of fruit per cluster (3.25), and number of fruit per plant (208.63), which revealed that genotypes could be selected from Cluster IV for these characters. The first three principal components (PC1, PC2, and PC3) accounted 73.99% of the total variation among the 24 genotypes. These phenotypic data increase the feasibility of prioritising breeding lines in a crossing programme based on the uniqueness of their desirable morphological traits.